2014
DOI: 10.1016/j.jpeds.2014.05.038
|View full text |Cite|
|
Sign up to set email alerts
|

Medical Status of 219 Children with Biliary Atresia Surviving Long-Term with Their Native Livers: Results from a North American Multicenter Consortium

Abstract: Objectives To examine the medical status of children with biliary atresia (BA) with their native livers after hepatic portoenterostomy (HPE) surgery. Study design The Childhood Liver Disease Research and Education Network (ChiLDREN) database was utilized to examine subjects with BA living with their native livers 5 or more years after HPE and to describe the prevalence of subjects with BA with an “ideal” outcome, defined as no clinical evidence of chronic liver disease, normal liver biochemical indices (aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 47 publications
3
85
0
2
Order By: Relevance
“…Recent reports indicate that those who develop bile flow (defined as a serum total bilirubin level <2 mg/dL) within 3 months of HPE have a >80% chance to be in the group of BA patients surviving with the native liver at 2 years of age . More importantly, although these patients are considered “successful” responders to Kasai HPE, at least 75% will develop ongoing fibrosis, portal hypertension, and cirrhosis, with significant risks of hepatic complications, death, and transplant from childhood through young adulthood . These BA patients are candidates for trials of an array of therapeutic agents as they have the potential to respond and stand to benefit significantly.…”
Section: Innovative Approaches To Treatmentmentioning
confidence: 99%
“…Recent reports indicate that those who develop bile flow (defined as a serum total bilirubin level <2 mg/dL) within 3 months of HPE have a >80% chance to be in the group of BA patients surviving with the native liver at 2 years of age . More importantly, although these patients are considered “successful” responders to Kasai HPE, at least 75% will develop ongoing fibrosis, portal hypertension, and cirrhosis, with significant risks of hepatic complications, death, and transplant from childhood through young adulthood . These BA patients are candidates for trials of an array of therapeutic agents as they have the potential to respond and stand to benefit significantly.…”
Section: Innovative Approaches To Treatmentmentioning
confidence: 99%
“…Most patients in their cohort experienced multiple episodes of cholangitis requiring hospitalization, with an average length of stay of 15 days. Ng et al 25 reported that 17% of 219 patients who retained their native livers at least 5 years after their Kasai operations had experienced an episode of cholangitis in the preceding year.…”
mentioning
confidence: 99%
“…Cholangitis is commonly seen early after the Kasai surgery. The majority of the patients surviving into adulthood without a transplant do not develop cholangitis and are not on any antibiotic prophylaxis [56]. Cholangitis, if it occurs, should be treated appropriately with intravenous or oral antibiotics depending on the clinical and biochemical severity at presentation.…”
Section: Biliary Atresiamentioning
confidence: 99%